Sensationalism versus substance: Building a framework that examines mass media coverage of migrants in the Italian context. (1st April 2019) - Coppini, David
Italy is at the forefront of the immigration and refugee crises that have characterized the European social landscape over the past ten years. In particular, attitudes towards migrants have become increasingly negative and political parties have used harsh rhetoric against migrants to appeal to anti-migrant sentiments in the population. Recently, acts of anti-immigrant violence have been at the centre of the public debate, placing media coverage of migration issues front and centre in the campaign for the legislative election of 2018. This article examines some of the themes that emerge from Italian media coverage on issues related to migration. In addition, this article proposes a framework to analyse the relationship between mass media, success of populist parties and the rise of anti-migrant attitudes.